Kontekstualność przemian polskiej szkoły - Rossa, Piotr (Uniwersytet im. Adama Mickiewicza w Poznaniu, Wydział Pedagogiczno-Artystyczny, 2018)
The text refers to antropological and cultural as well as sociological-pedagogical approaches to analyse the challenges of the modern world towards the Polish school. Such a wide analysis, going beyond the school environment itself, allowed to outline the ongoing cultural changes, that are bringing many new opportunities with them, as well as posing treeats on the roads to obtaining ethical orientation and the hierarchy of values in the home and school education. In the introduction, I showed the dissimilarity of 20th-century historical experiences for particular regions of Europe, an at the end I made an assessment of the changes taking place in the contemporary Polish educational system and their impact on tasks for parents, teachers and educators.
Contextuality of Changes in the Polish School
Keywords: polska szkoła; rodzina; wychowanie; Internet; media; dzieci w sieci; wielokulturowość; tożsamość; education; globalization; pamilya; οικογένεια; 家庭; परिवार; valor; sviluppo scientifico; educazione; globalizzazione; transformation of the Polish school; преобразование польской школы; 迁移; 身分; 全球化; Küreselleşme; Kimlik